Antimicrobial activity of olive oil against microbial infections - Alqahtani, Monerah Saleh Alhlass (Journal of medical and pharmaceutical sciences, 2019)
Olive oil and olive extracts have been used in folk medicine since ancient times. Romans and Greeks employed olive extracts to treat many diseases and an extract of boiled olive leaves was administered as a drink to malaria patients during the 19th century. Hence, the Mediterranean countries have cultivated the olive tree (Olea europaea L.) to produce olive oil, table olives and olive leaf extracts for centuries. At present, both olive oil and table olives are important components of the Mediterranean diet and are largely consumed throughout the world. In addition, there are many enterprises that commercialize olive leaf extracts to treat a myriad of diseases, many of them caused by microorganisms. Recently, the importance of preventive medicine has been gradually recognized in the field of orthopaedic surgery with a concept that peak bone mass should be increased in childhood as much as possible for the prevention of osteoporosis (Ohtani et al., 2009). The aim of the current study is to explore the antimicrobial activity of olive oil against microbial infections. To achieve the aim of research, the researcher applied the exploratory approach where dozens of relevant studies were reviewed and explored in order to collect the results needed to enrich the discussion within the current study. The results of study indicated the efficiency of antimicrobial activity of olive oil against microbial infections.